Dexmedetomidine Relieves Neuropathic Pain in Rats With Chronic Constriction Injury via the Keap1–Nrf2 Pathway - Liu, Yatao; Liu, Wei; Wang, Xiao-Qing; Wan, Zhan-Hai; Liu, Yong-Qiang; Zhang, Meng-Jie (Frontiers in Cell and Developmental Biology, 2021)
This study aimed to determine the role of dexmedetomidine (Dex) in neuropathic pain (NP) after chronic constriction injury (CCI) in a rat model as well as its underlying mechanism. First, a CCI rat model was established. After treatment with Dex, the severity of NP was ascertained by monitoring paw withdrawal threshold (PWT) and paw withdrawal latency (PWL) at different time points. Immunohistochemical analysis was performed to determine the levels of Keap1 and Nrf2 in the spinal cord. Furthermore, the levels of Keap1–Nrf2–HO-1 pathway molecules, apoptotic proteins, and antioxidant genes in the spinal cord or isolated primary microglia were determined using quantitative polymerase chain reaction and western blotting. The release of proinflammatory cytokines was detected via enzyme-linked immunosorbent assay. To evaluate Dex-treated CCI-induced NP via the Keap1–Nrf2–HO-1 pathway, the rats were intrathecally injected with lentivirus to upregulate or downregulate the expression of Keap1. We found that Dex inhibited pathological changes and alleviated sciatic nerve pain as well as repressed inflammation, apoptosis, and redox disorders of the spinal cord in CCI rats. Keap1 protein expression was substantially downregulated, whereas Nrf2 and HO-1 expressions were significantly upregulated in the spinal cord after Dex administration. Additionally, Keap1 overexpression counteracted Dex-mediated inhibition of NP. Keap1 overexpression led to a decrease in Nrf2 and HO-1 levels as well as PWT and PWL but led to an aggravation of inflammation and antioxidant disorders and increased apoptosis. Keap1 silencing alleviated NP in rats with CCI, as evidenced by an increase in PWT and PWL. Keap1 depletion resulted in the alleviation of inflammation and spinal cord tissue injury in CCI rats. Collectively, these findings suggest that Dex inhibits the Keap1–Nrf2–HO-1-related antioxidant response, inflammation, and apoptosis, thereby alleviating NP in CCI rats.